2009
DOI: 10.1039/b815099k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of functional molecular rod oligomers

Abstract: We are presenting the synthesis of a phenylene ethynylene-based rod containing an Fmoc protected amino group and an activated acid which can be applied to peptide couplings. This linear amino acid analogue is applied to the synthesis of di-, tri- and pentamers. The pentamer has a molecular mass of 6.5 kDa and is characterized by (1)H NMR spectroscopy and MALDI-TOF MS. The method has potential for the formation of long macromolecular oligomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Current interest in DPA stems from its use as a rod-like energy and electron conducting unit in conjugated polymers, dendrimers, and molecular photonic devices. , Moreover, photoexcitation of derivatives of DPA leads to efficient double-strand DNA cleavage and cancer cell apoptosis …”
Section: Introductionmentioning
confidence: 99%
“…Current interest in DPA stems from its use as a rod-like energy and electron conducting unit in conjugated polymers, dendrimers, and molecular photonic devices. , Moreover, photoexcitation of derivatives of DPA leads to efficient double-strand DNA cleavage and cancer cell apoptosis …”
Section: Introductionmentioning
confidence: 99%
“…6 Model systems containing oligo(ethylene, acetylene, phenylene)-based components have been extensively investigated using various experimental methods 7 and synthetic work is ongoing. 8 When such p-conjugated systems are incorporated in solid-state devices, one important aspect from the electronic structure point of view is the nature of the coupling of the organic molecule to the electrode and the manner in which this affects charge injection into the wire. 9 In this context, properties like the ionization potential and band gap of the wire are important, and the ability to compare accurately calculated values and experimental values offers the potential to lead to a better understanding of the physical and chemical properties of conjugated polymers, [10][11][12][13] particularly in as much as ionization potentials and band gaps in the organic wire can be modified by chemical substitution in much the same fashion as Fermi levels in solids may be modified by doping.…”
Section: Introductionmentioning
confidence: 99%
“…Both monomers (5 and 7) needed for the Sonogashira polymerization reaction were synthesized via similar pathways (Scheme 2). 18 From 1 H NMR analysis it was observed that some of the bromine atoms on the alkyl side chains were replaced by iodine during this reaction, leading to an extra triplet at 3.18 ppm (Fig. A large excess of 1,8-dibromooctane was used to prevent two-fold reaction on one alkyl chain and potassium carbonate was found to give better yields than sodium hydroxide 16 or sodium hydride (in ethanol).…”
Section: Resultsmentioning
confidence: 99%
“…Pd(PPh 3 ) 2 Cl 2 was used as the catalyst and CuI as the co-catalyst. 18 From 1 H NMR analysis it was observed that some of the bromine atoms on the alkyl side chains were replaced by iodine during this reaction, leading to an extra triplet at 3.18 ppm (Fig. S2 †).…”
Section: Polymer Chemistry Papermentioning
confidence: 99%